WED025DATA - Weddell Sea limited region ocean ice shelf model (NEMO) data - Bull, Christopher (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2020)
This dataset contains Weddell Sea limited region ocean ice shelf model (NEMO) outputs. The included experiments were designed to look at the influence of far-field changes in temperature and salinity to changes in melt rates in the Filchner-Ronne Ice Shelf melt rate. Funding was provided by the Filchner Ice Shelf System project NE/L013770/1. : The scripts used to prepare the regional model configuration, and model components are available on https://doi.org/10.5281/zenodo.3909234.